Design, Synthesis, and Anti-Tubercular Studies of 10-(phenylsulfonyl)pyrimido[1,2-a]benzimidazol (10H) One Derivatives - Jagannath, K. V.; Krishnamurthy, G. (New Innovations in Chemistry and Biochemistry Vol. 3, 2021)
Sulfonamides are unique class of compounds possessing exceptional antibacterial activity. Sulpha drugs were the first effective chemotherapeutic agents to be widely used for the cure of bacterial infection in human and found to be resisted on Mycobacterium tuberculosis, Typhoid and Paratyphoid bacilli etc. A series of novel 10-phenylsulfonyl-2-substituted-4,10 dihydrobenzo[4,5]imidazo[1,2- a]pyrimidin-4-one derivatives obtained from N-sulfonation of 2-substituted-pyrimido[1,2- a]benzimidazol-4(10H)-ones and screened for their in vitro anti-tuberculosis activities against Mycobacterium tuberculosis H37Rv by Microplate Alamar Blue Assay (MABA) method.